Cirrhosis regression in hepatitis C patients with sustained virological response after antiviral therapy: a meta‐analysis. (22nd May 2014) - Akhtar, Ehsaan; Manne, Vignan; Saab, Sammy
Abstract Background & Aims Chronic hepatitis C may be associated with cirrhosis, liver failure and hepatocellular carcinoma. Studies have demonstrated improved clinical outcome in patients who achieved a sustained viral response (SVR). Methods A systematic literature search was performed to identify studies that assessed the association between SVR and cirrhosis regression. The main outcome studied was cirrhosis regression in patients with a SVR as compared with patients without a SVR. Six studies totalling 443 patients were included. Dichotomous outcomes were reported as risk ratios (RR) with 95% confidence intervals (CI). Results Of the 443 patients with cirrhosis, 137 achieved a SVR. Of these 137 patients who achieved an SVR, 73 (53%) patients had regression of cirrhosis. The risk ratio of cirrhosis regression was 2.69 [Confidence Interval (CI) 1.45–4.97, P < 0.01] in patients who achieved a SVR. The risk of cirrhosis regression was consistently in favour of patients who achieved a SVR regardless of the length of the biopsy or whether the biopsy was reviewed by a single or multiple pathologists. The risk ratio of cirrhosis regression was related to the duration of follow‐up between biopsies. The relative risk for regression of cirrhosis in studies in which the mean or median time for the follow‐up liver biopsy was greater than 36‐month was 4.33 (CI 1.1–17.0, P = 0.04) as compared to a relative risk of 1.79 (CI 1.26–2.29, P < 0.01) in studies with a mean or median time between the follow‐up biopsy of less than 36‐month. Conclusions Our results suggest that the majority of patients with cirrhosis who achieve a SVR develop cirrhosis regression. Time between biopsies appears to be an important determinant of the likelihood of cirrhosis regression.